Analisis Persepsi Siswa, Guru, dan Dunia Usaha/Dunia Industri (DUDI) dalam Penempatan PKL bagi Kelas XI Jurusan Teknik Komputer dan Jaringan SMK Negeri 2 Malang - Syamsu Anaqin; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There are problems during the implementation of Job Training, namely the placement of students who are still not by the competencies they have. And students get jobs that are not by their fields of competence. Placement of street vendors is only still considering one factor, domicile or residence. As well as the existence of obstacles or obstacles experienced during the implementation of street vendors. Based on the problems that have been found, this study aims to determine the perceptions of students, teachers, and DUDI in determining the placement of street vendors and the obstacles experienced in the implementation of street vendors. The research method uses quantitative descriptive methods. Data collection techniques used were interviews, questionnaires, and observations. The study was conducted at State Vocational High School 2 Malang with the subject of research in class XII students of Computer and Network Engineering majors as many as 84 students, productive teachers as many as 4 people, and DUDI as many as 3 people. The results showed that there were several similar views when viewed from student questionnaires, teacher interviews, and DUDI interviews. The same variables of the three are academic, residence, readiness, and constraints.